PENGARUH LATIHAN CIRCUIT TRAINING TERHADAP PENINGKATAN VO2MAX - Reza Ramadani; Padli Padli; Sari Mariati; Roma Irawan (Performa, 2020)
The problem in this study is that Vo2Max is still low due to lack of aerobic endurance and one of the exercises for aerobic endurance to improve Vo2Max is circuit training. The independent variable in this study is circuit training, and the dependent variable in this study is the increase in Vo2Max. The purpose of this study was to see the extent of the effect of circuit training on the increase in Vo2Max of basketball players at SMA Negeri 14 Padang City. This type of research is a quasi-experimental. The population in this study were all basketball players at SMA Negeri 14 Kota Padang who actively participated in training activities in 2020 as many as 58 people. The sampling technique in this study used purposive sampling technique, so the number of samples in this study were 14 male players in class XI SMA. Negeri 14 Padang City. The research instrument was an increase in Vo2Max for basketball players at SMA Negeri 14 Padang City. The study was conducted in July-August 2020, the data analysis technique in this study used the t test. Based on the results of research and hypothesis testing, it can be concluded that there is a significant effect of the training circuit training method on the increase in Vo2Max basketball players at SMA Negeri 14 Padang City, this is evidenced by the tcount of 10.39 while the t table is 1.77 with a significant level of α = 0 , 05.